A NaNi0.5Mn0.5SnxO2 cathode with anti-structural deformation enhancing long lifespan and super power for a sodium ion battery. Issue 58 (16th June 2020) - Meng, Yiming; An, Juan; Chen, Lei; Chen, Guorong; Shi, Liyi; Lu, Mi; Zhang, Dengsong
Abstract : Introduction of Sn 4+ enlarges the interlayer spacing and builds a heteroatomic skeleton preventing multiphase transition of O3-NaNi0.5 Mn0.5 O2 for a sodium ion battery. Abstract : The enlarged interlayer spacing in NaNi0.5 Mn0.5 O by doping with Sn 4+ prevents TMO2 slips and eliminates irreversible multiphase transitions during cycling, achieving a high capacity of 191 mA h g −1 at 0.1C for half cells, as well as 1000 long cycles at 1C and high power ability at 50C for the full cell.